Drosophila screening model for metastasis: semaphorin 5c is required for l(2)gl cancer phenotype. - Woodhouse, E.C.; Fisher, A.; Bandle, R.W.; Bryant-Greenwood, B.; Charboneau, L.; Petricoin, E.F.; Liotta, L.A. (Proceedings of the National Academy of Sciences of the United States of America, 2003)
Cancer metastasis is a complex process involving many genes and pathways. This complexity hinders the identification of molecules functionally required for this process. We have developed and used a Drosophila screening system to identify genes that are functionally important for tumorigenicity and metastasis. Deletion of Drosophila lethal giant larvae (l(2)gl) leads to highly invasive and widely metastatic tumors on transplantation into adult flies. Random homozygous P element insertions were screened for the ability to modulate the l(2)gl phenotype. Analysis of metastasis patterns of the lines containing P element insertions and lacking wild-type l(2)gl expression identified three homozygous mutations that dramatically alter tumorigenesis and/or metastasis. Semaphorin 5c (Sema 5c) is required for tumorigenicity, apontic overexpression suppresses metastasis but not tumorigenicity, and pointed up-regulation accelerates lethality of l(2)gl tumors. Furthermore, class 5 semaphorins are shown to be expressed in cancer cells and localized to the membrane. Drosophila Sema-5c and the mammalian homologs are transmembrane proteins with extracellular thrombospondin type I (TspI) repeats. TspI repeats are known in some proteins to bind and activate transforming growth factor (TGF)-beta ligand. Phospho-Mad and the downstream target gene vestigial were elevated in l(2)gl tumors, thus linking Drosophila neoplasia to the Dpp (TGF-beta-like) signal pathway. The activation of the Dpp pathway in l(2)gl tumors occurred only in the presence of Sema-5c. This study demonstrates that the power of Drosophila genetics can be applied to screen, identify, and characterize molecules that are functionally required for invasion and metastasis.